Application and comparison of analytic accelerated test-models for lifetime prediction of a novel contacting method - Spahr, Michael; Kreitlein, Sven; Haas, Raphael; Jaumann, Andreas; Gläßel, Tobias; Spreng, Simon; Franke, Jörg (2016 IEEE 62st Holm Conference, 2016)

Challenges in the Manufacturing of Hairpin Windings and Application Opportunities of Infrared Lasers for the Contacting Process - Gläßel, Tobias; Seefried, Johannes; Franke, Jörg (2017 7th International Electric Drives Production Conference (EDPC), 2017)

Challenges of the Hairpin Technology for Production Techniques - Riedel, Andreas; Masuch, Michael; Weigelt, Michael; Gläßel, Tobias; Kühl, Alexander; Reinstein, Sebastian; Franke, Jörg (2018 21st International Conference on Electrical Machines and Systems (ICEMS), 2018)
The electrification of the drive train of passenger cars is currently undergoing an evolution from windings previously drawn in, which are known from industrially used electrical machines, to windings specially tailored to the requirements of mobile electric traction. A main trend is the use of pluggable shape windings, so-called hairpins. In order to fully exploit the economic advantages of this winding, elaborated production concepts and strategies are required. Due to the novelty and the currently ongoing innovation of these type of windings, the differentiated manufacturing possibilities per process step have not yet been fully defined. In view of the economic efficiency, high process speeds with increasing process reliability play a major role. The aim of this paper is to show a process chain of hairpin technology that is as universally valid as possible, to name the different alternatives for each process step and to explain their characteristic
Keywords: Wires; Windings; Insulation; Manufacturing automation; Production systems; Conductors; Hairpin; Process Chain; Production Technologies

Development, qualification and optimization of innovative contacting methods in the field of electric drives production - Gläßel, Tobias; Spahr, Michael; Spreng, Simon; Franke, Jörg (Zeitschrift für wirtschaftlichen Fabrikbetrieb, 2016)
Regarding the demands for newly developed engine designs as well as the production related requests for processes enabling flexible mass production, the dynamic field of electrical engine production is facing more and more needs to utilize optimization potentials. As these needs especially influence the stator contacting process, the institute FAPS introduced the research group contacting technologies, which uses a multidimensional approach to obtain the complexity of the regarded research field. Here, not only already existing technologies are further optimized but also new technologies are developed and qualified.

Elektromotorenproduktion 4.0: Potenziale des maschinellen Lernens in der Elektromotorenproduktion am Beispiel des Laserschweißens von Hairpins - Mayr, Andreas; Lutz, Benjamin; Weigelt, Michael; Gläßel, Tobias; Seefried, Johannes; Kißkalt, Dominik; Franke, Jörg (Zeitschrift für wirtschaftlichen Fabrikbetrieb, 2019)

Evaluation of Machine Learning for Quality Monitoring of Laser Welding Using the Example of the Contacting of Hairpin Windings - Mayr, Andreas; Lutz, Benjamin; Weigelt, Michael; Gläßel, Tobias; Kißkalt, Dominik; Masuch, Michael; Riedel, Andreas; Franke, Jörg (8th International Electric Drives Production Conference (EDPC), 2018)

Evaluation of monitoring approaches for the ultrasonic crimping process of tubular cable lugs - Seefried, Johannes; Gläßel, Tobias; Zürn, Marcel; Franke, Jörg (Proceedings of the 7th International Electric Drives Production Conference (EDPC), 2017)
Keywords: Temperature measurement; monitoring; crimping; welding; ultrasonic crimping

Evaluation of the influence of varying electrode materials within the thermo-crimping process - Spreng, Simon; Gläßel, Tobias; Hoetzel, Stefan; Schäfer, Heiko; Wunder, David; Franke, Jörg (2015 5th International Conference on Electric Drives Production, EDPC 2015 - Proceedings, 2015)
In the field of electric drives manufacturing, the thermo-crimping process is one major technology to join insulated copper wires with belonging current carrying parts. However, due to its operating principle, this technology has to be associated with strong disadvantages e.g. the excessive tool attrition leading to an immoderate amount of maintenance operations. For this reason, this paper focuses on the investigation of varying crimping electrode materials, whereas the objectives product quality, tool attrition and process energy are analyzed.
CRIS-Team Scopus Importer:2023-03-07
Keywords: crimping tool; electric drives manufacturing; joining; thermo-crimping

Experimental Evaluation of Tool Geometries for the Ultrasonic Crimping Process for Tubular Cable Lugs - Seefried, Johannes; Gläßel, Tobias; Kühl, Alexander; Mayr, Andreas; Franke, Jörg (2019 IEEE Holm Conference on Electrical Contacts, 2019)
In the production chain of electric drives, the electrical and mechanical contacting of the winding ends with a contact element is a time-consuming and cost-intensive process step. The most common processes, e.g., hot crimping, are characterized by high tool wear and enormous energy consumption. An innovative and at the same time energy- efficient process is the ultrasonic crimping process which also combines the two process steps of skinning and contacting in a single process. The thermal energy required for skinning is based on the damping of oscillation energy in the cable lugs used. Due to the direct heat generation in the cable lug and the oscillations coupled in, the process has high potentials with regard to process stability, contacting of high-frequency litz wires and energy consumption. However, some disadvantages like the occasional occurrence of fatigue fractures in the tubular cable lugs and unclear dependencies reducing process reliability have to be investigated. One possibility to avoid the cracks and to further increase the process stability of ultrasonic crimping is the evaluation of adapted tool geometries. In the context of this paper, different sonotrode and anvil geometries are compared and evaluated with regard to electrical, mechanical and visual connection quality.<br

Explicit FEM analysis of a new contacting method for electronic devices with novel wiring harnesses - Spahr, Michael; Bönig, Jochen; Gläßel, Tobias; Spreng, Simon; Ebert, T.; Franke, Jörg (61st IEEE Holm Conference on Electrical Contacts, HOLM 2015, 2015)
Through customers' desire for an individualization of vehicles, new electronics-supported functions are continuously being added. The automobile wiring harness must meet these requests without any further increase of weight and volume. The basic trend towards a modular vehicular design, the continually growing complexity of production and assembly processes, supports the use of flexible flat cables (FFCs) in a hybrid wiring system architecture. For an integral approach, it is also important to develop corresponding alternatives for electrically contacting FFCs with the components. To that end, the process-conditional, one-sided accessibility of FFCs represents a particular challenge. Motivated by these challenges, the Institute FAPS has developed an automated assembly system of FFCs and a new concept for a flexible electric contacting system enabling direct electrical contacting of installed FFCs. The scope of this approach is the analysis of the new contacting method by means of an explicit finite element analysis (FEA). For this purpose, a numerical model was developed that enables the simulation and optimization of the contacting process and its important parameters. In a second step, the results of the FEA are validated by respective experiments.
Keywords: contact area; contact force; contact resistance; electrical contact; finite element modelling; flexible flat cable

Influence of Enameled Wire Preparation on the Laser welding of Hairpin Windings - Gläßel, Tobias; Riedel, Andreas; Franke, Jörg; Kühl, Alexander (2022 IEEE 67TH HOLM CONFERENCE ON ELECTRICAL CONTACTS (HLM), 2022)
CRIS-Team WoS Importer:2023-02-10

Infrared laser based contacting of bar-wound windings in the field of electric drives production - Gläßel, Tobias; Baat, Florian; Schwinghammer, Daniel; Seefried, Johannes; Kühl, Alexander; Franke, Jörg (Procedia CIRP, Volume 74, 2018)
Driven by electric mobility innovative winding methods increasing the copper fill ratio and thus the power density of electrical drives gain in importance. Compared to conventional windings, bar-wound windings based on rectangular cross sections besides optimized copper fill ratios also offer advantages in terms of automated production. Because of the high number of joints necessary for the manufacturing of the winding, contacting efforts increase significantly wherefore the process of laser welding, due to its short process times and high reproducibility shows potentials to realize the process step. This paper examines the most important interactions within the process of laser welding of insulated copper wires with rectangular cross sections in the context of electric drives production. Besides workpiece specific factors, the focus is set on process parameters, beam guidance strategies and specific quality requirements. For this purpose, a parameter study based on design of experiments is executed in which suitable measuring technologies are used to quantify the properties of the samples. <br
Keywords: laser beam welding; infrared lasers; insulated copper conductors; hairpin windings; electrical contacts

Innovative Kontaktierungstechnologien im Elektromaschinenbau Entwicklung, Qualifizierung und Optimierung - Gläßel, Tobias; Spreng, Simon; Spahr, Michael; Franke, Jörg (Zeitschrift für wirtschaftlichen Fabrikbetrieb, 2016)
Im sich dynamisch entwickelnden Feld der elektrischen Antriebstechnik stellen neue, von der Automobilindustrie getriebene Motortopologien sowie die Forderung nach serienflexiblen Prozessen die zentralen Treiber zur Entwicklung innovativer Kontaktierungsverfahren dar. Die Arbeitsgruppe Kontaktierungstechnologien begegnet diesem Spannungsfeld mit einem multidimensionalen Ansatz, der aus der Weiterentwicklung bestehender und aus der Erforschung neuartiger Kontaktierungslösungen besteht.
Keywords: Kontaktierungstechnologien; elektrische Maschinen

Kontaktierung von Antrieben für die Elektromobilität - Gläßel, Tobias; Franke, Jörg (Zeitschrift für wirtschaftlichen Fabrikbetrieb, 2017)
Getrieben durch die Elektromobilität und neuen Anforderungen hinsichtlich Stückzahlen, Qualität und innovativer Motorauslegungen rücken Produktionstechnologien für die Wicklung elektrischer Antriebe in den Fokus. Insbesondere etablierte Kontaktierungstechnologien, mit deren Hilfe lackisolierte Leiter elektrisch und mechanisch verbunden werden, können nur bedingt Schritt halten. Der Beitrag identifiziert aktuelle Anforderungen an Kontaktierungstechnologien und stellt innovative Lösungsansätze vor.
Keywords: Elektromobilität; elektrische Antriebe; Kontaktierungstechnologien

Kontaktierung von Antrieben für die Elektromobilität: Innovative Vorgehensweisen, Prozessketten und Technologien - Gläßel, Tobias; Franke, Jörg (Zeitschrift für wirtschaftlichen Fabrikbetrieb, 2017)
Impelled by electromobility and new requirements concerning quantity, quality and innovative designs of drives, production processes for the winding of electric machines gain in importance. Especially established contacting technologies that are used to connect enameled wires electrically and mechanically are not able to keep abreast of this development. This article identifies current requirements for contacting technologies and showcases innovative solution approaches.
CRIS-Team Scopus Importer:2023-03-07

Kontaktierverfahren für lackisolierte Leiter - Gläßel, Tobias; Spreng, Simon; Franke, Jörg (2018)

Manufacturing Influences on the Motor Performance of Traction Drives with Hairpin Winding - Gläßel, Tobias; Bachinski Pinhal, Daniel; Masuch, Michael; Gerling, Dieter; Franke, Jörg (2019 9th International Electric Drives Production Conference (EDPC), 2019)
To face the challenges posed by the electrification of the automotive drivetrain, rotating electrical machines are getting an impetus to innovation. Thus, machines of high power density are required to be manufactured cost-effectively in a large-scale production. To meet these requirements, the application of stators with hairpin windings is focused in industry and research institutions, as they show potentials to realize improved copper fill ratios in the armature slots. In addition, this technology also is seen as one possibility to substitute the elaborate winding technologies that often feature a lack of reproducibility, by bending, assembling and joining processes. During the design of electric drives, the influences of deviations of manufacturing processes on its performance usually are not taken into account. This particularly applies to the technology of hairpin windings, whose manufacturing requires a large number of bending and contacting operations. These process steps may influence the electrical properties of the winding, changing the behavior of the electrical machine. For this reason, the objective of this paper is to identify deviations in the manufacturing processes of hairpin windings and to validate their influence on the performance of the drive. For this purpose, measuring systems are set up which make it possible to quantify the influence of bending and contacting processes on the electrical properties of the winding by means of highly accurate resistance measurements. As next step, a simulation is set up to map the production influences on the hairpin winding to the machine’s efficiency. Based on simulation studies, the influences of the manufacturing imperfections on the engine performance become visible. <br
Keywords: Electric Drives Production; Hairpin Windings; Manufacturing Influences

Optimization of the Process Reliability of the Ultrasonic Crimping Process by Evaluating the Mounting Conditions for Tubular Cable Lugs - Seefried, Johannes; Gläßel, Tobias; Rezler, Raphael; Franke, Jörg (Energy Efficiency in Strategy of Sustainable Production IV, 2018)

Potentials of an Explicit Finite Element Analysis of the Bending Processes for Coated Copper Wires - Weigelt, Michael; Riedel, Andreas; Masuch, Michael; Mahr, Alexander; Gläßel, Tobias; Franke, Jörg (2017 7th International Electric Drives Production Conference (E|DPC), 2017)
The advancing electrification in industry and everyday life requires powerful electric drives providing highest efficiency. The winding as the core of these drives is subject to continuous development. Furthermore, it is of decisive importance to accelerate sample production for prototype construction and small series production of electric drives to shorten the innovation cycles. Coated bar-wound winding elements are increasingly important for the application in electric drives. The process window for damage free bending processes of coated copper wires is yet not defined. Structural mechanical finite element (FE) modelling is therefore a powerful tool to reduce costly trial-and-error loops and shortening development cycles for those production techniques as it provides reliable quantitative results. The aim of this paper is to propose the basics for defining a process window for the bending of flat wires using experimental bending test setups and FE-simulation tool
Keywords: finite element method; bending; flat wire

Process Reliable Laser Welding of Hairpin Windings for Automotive Traction Drives - Gläßel, Tobias; Seefried, Johannes; Masuch, Michael; Riedel, Andreas; Mayr, Andreas; Kühl, Alexander; Franke, Jörg (IEEE International Conference on Engineering, Science, and Industrial Applications (ICESI), 2019)
Keywords: Electric Drives Production; Hairpin Winding; Contacting Technologies

Qualification of main impacts on the inductive skinning process of copper wire bundles - Spreng, Simon; Borngraeber, Thorsten; Gläßel, Tobias; Franke, Jörg (ICEC 2016 - 28th International Conference on Electric Contacts, 2016)
Aside from the distinct contacting process, within the field of electric drives production, the quality of the isolation skinning process has to be assured. One promising technology in this context is the inductive skinning process, which utilizes skin and proximity effects occurring at high-frequency alternating currents. By the use of these physical impacts, the surface of insulated copper materials can be strongly heated up in short process times, leading to an extensive removal of the thermosetting insulation coatings. The following paper presents the results, which were experienced by using an inductive skinning machine with frequencies of 280 kHz. Here, insulated copper wire bundles serve as application example, whereby the number and size of copper wires, as well as the insulation type is varied. Subsequently, different technologies e.g. mechanical and magnetic crimping to perform the following contacting process are qualified and evaluated against each other.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Electric drives manufacturing; Inductive skinning; Joining process

Quantification of the influence of varying electrode shapes and materials on the thermo-crimping process of standardized tubular cable lugs - Spreng, Simon; Gläßel, Tobias; Muselmann, Johannes; Wörrlein, Marina; Franke, Jörg (2016 6th International Electric Drives Production Conference, EDPC 2016 - Proceedings, 2016)
The main joining task in the field of electric drives production is to connect bundles of insulated copper wires with standardized tubular cable lugs, as this connection alternative is widely used in all types of different electrical stator varieties. Implementing this process in industrial production facilities, the thermo-crimping technology is widely used. Within this technique, the insulation is thermally destroyed, while coincidently, the tubular cable lug and the inlying skinned copper wires are deformed plastically, which generates a force fit crimp-connection. The thermo-crimping process features strong production-related benefits such as short tact times, high process reliabilities as well as an easy process handling. The severe disadvantage however has to be seen within the electrode wearing, as the crimping tools are simultaneously exposed to high pressures and temperatures of at least 600 C reducing an electrode's number of possible crimping routines to at most 1500. As a consequence, especially in serial production, excessive maintenance efforts have to be taken into account, strongly reducing the production efficiency. For this purpose, the institute FAPS focuses its research on the reduction of tool wearing. Beginning with a theoretical process analysis, different tool shapes and materials are compared experimentally considering both, the joint quality and the electrode wearing. Subsequently, regression models are introduced predicting static quality properties such as tensile forces and transition resistances. Finally, the proposed model is validated by applying the found formula to different cable lug sizes.
CRIS-Team Scopus Importer:2023-03-07
Keywords: electric drives manufacturing; thermo crimping; varying electrode shapes

Robot-based Production of Electric Motors with Hairpin Winding Technolgy - Kühl, Alexander; Riedel, Andreas; Vogel, Alexander; Hartl, Sebastian; Gläßel, Tobias; Franke, Jörg (International Conference on Intelligent Automation and Robotics (ICIAR'19), 2019)

Schlussbericht zu dem Teilvorhaben "Automatisierte Fertigungstechnologien zum Biegen, Montieren und Schalten von innovativen Formspulenwicklungen" im Verbundprojekt "PRO-E-Traktion" - Gläßel, Tobias; Masuch, Michael; Weigelt, Michael; Kühl, Alexander; Franke, Jörg (2020)
Schlussbericht zu dem Teilvorhaben "Automatisierte Fertigungstechnologien zum Biegen, Montieren und Schalten von innovativen Formspulenwicklungen" im Verbundprojekt "PRO-E-Traktion" ("Automatisierte und robuste Produktionssysteme für E-Traktionsantriebe") Gefördert durch das Bundesministerium für Wirtschaft und Technologie, begleitet durch DLR e. V. Projektträger Förderkennzeichen: 01MX15011F Die Formspulentechnologie gilt als Schlüssel zur Realisierung leistungsdichter elektrischer Traktionsantriebe. Darüber hinaus stellt sie eine Möglichkeit dar, die gegenwärtig schlecht kontrollierbaren Wickelverfahren durch stabilere Biege-, Montage- und Fügeprozesse zu ersetzen. Allerdings waren zum Zeitpunkt des Projektbeginns die benötigten Technologien weder identifiziert, noch entwickelt und qualifiziert. Hier setzt das vorliegende Projekt an, indem es technologische Alternativen für die durchzuführenden Prozessschritte identifiziert und priorisiert. Basierend darauf werden vollautomatisierte Prozessketten zur Herstellung von Statoren mit Hairpinwicklung in unterschiedlichen Stückzahlszenarien konzipiert und in Simulationen validiert. Um darüber hinaus Potentiale alternativer Arten offener Formspulenwicklungen bewerten und gegenüberstellen zu können wird eine Referenzmaschine auf diese übertragen und eine Bewertungssystematik entwickelt und angewandt, in deren Ergebnis die produkt- und fertigungsseitigen Potentiale von Hairpinwicklungen bestätigt werden. Die identifizierten Kernprozesse des Biegens, Montierens sowie der Kontaktierung werden grundlegend analysiert und auf dieser Grundlage die Industrialisierbarkeit der Prozesse abgeleitet. Für die Herstellung der Hairpins zeigt sich eine Kombination des Rotationszugbiegeverfahrens mit einem Gesenkbiegeverfahren als aussichtsreich. Zur Montage der Hairpins in den Stator werden unterschiedliche Konzepte ausgearbeitet und validiert, wobei die Wichtigkeit einer geeigneten Führung der Formspulen herausgearbeitet wurde. Es zeigt sich, dass der Kontaktierung eine wesentliche Rolle in der Prozesskette zukommt, wobei gezeigt wird, dass sich mit einer Kombination aus laserbasierten Isolationsabtrag und Laserstrahlschweißen ein geeigneter Kontaktierungsprozess ableiten lässt. Die erzielten Ergebnisse tragen zu einer Senkung der Hürde bei der vollautomatisierten Herstellung von Statoren mit Formspulen-wicklung bei, da sie die Technologieauswahl, Prozessentwicklung sowie Anlagenplanung maßgeblich vereinfachen Bar-wound windings are regarded to be a key technology to realize electric traction drives with a high power density. Additionally, they provide an opportunity to replace recent winding technologies, that are characterized by a poor controllability, with bending, assembling and joining processes featuring a better process stability. Nevertheless, at the beginning of this project the technologies necessary were neither identified nor developed and qualified. To deal with these issues, the present project identifies and assesses technological alternatives for the process steps necessary. On that basis fully automated production chains for the production of stators with hairpin windings for different production volumes are designed and validated in simulations. Beyond that, the reference winding of this project is conveyed on alternative kinds of bar-wound windings. To be able to compare the resulting concepts, a rating system for bar-wound windings is developed that confirms the potentials of hairpin windings. The key process steps of bending, assembling and contacting identified in this project are analyzed fundamentally and based on these results, industrialization capabilities are derived. For the production of the hairpins, a combination of rotary draw bending and die bending proves to be promising. Different concepts to assemble the hairpins to the lamination are developed and analyzed. It is determined, that a suitable guidance of the bar-wound coil is necessary in any case. The analysis of the contacting process showed, that this process plays an important role in the process chain. Combining a laser based process for the removal of the insulation with a laser welding process is a suitable possibility to realize a reproducible contacting process. The results achieved contribute to a reduction of obstacles for the implementation of a fully automated production of stators with bar-wound windings, as they facilitate the selection of suitable technologies, the development of processes necessary and the planning of production facilities.
Keywords: bar-wound windings; Bending; Biegen; electric mobility; Elektromobilität; Elektromotor; enamelled wire; FKZ: 01MX15011F; Formspulenwicklung; Hairpin; hairpin windings; Hairpinwicklung; INSULATION; Isolation; Lackdraht; Laserschweißen; production technologies; Produktionstechnologien; Pro-E-Traktion; Stator; traction drives; Traktionsantriebe

Skinning of Insulated Copper Wires within the Production Chain of Hairpin Windings for Electric Traction Drives - Gläßel, Tobias; Seefried, Johannes; Kühl, Alexander; Franke, Jörg (International Journal of Mechanical Engineering and Robotics Research, 2019)
Due to the influence of electric mobility drives used in the automotive powertrain are experiencing a boost in innovation. Caused by the accompanying demand for an increase in power density and the necessity to reduce costs in series production, the winding of electric machines and associated production processes are being improved. A promising novel type of winding is the bar-wound winding, which, in addition to numerous advantages, poses new demands on technologies for their production. In this case the winding is manufactured from a wide range of preformed elements made of enamelled copper wire, which must be connected to each other mechanically and electrically. For this purpose it is necessary to remove the insulation made of thermosetting material from the conducting elements in the joining area. Due to the large number of contacts that have to be prepared in this way, it gets essential to use productive and in particular process-safe skinning technologies. In this paper, the motivation for the application of bar-wound windings and the corresponding production chain is expounded. A method for the metrological quality control of residues in the skinned area is qualified and technologies for the realization of the skinning process are compared. In addition, experiments to create process knowledge for the laser-based removal of the insulation and the skinning by means of rotating brushes are presented.<br
Keywords: electric drives production; electric traction drives; hairpin winding; laser-based skinning; fluorescence based quality assurance

Skinning of insulated copper wires within the production chain of hairpin windings for electric traction drives - Gläßel, Tobias; Seefried, Johannes; Kühl, Alexander; Franke, Jörg (International Journal of Mechanical Engineering and Robotics Research, 2020)
Due to the influence of electric mobility drives used in the automotive powertrain are experiencing a boost in innovation. Caused by the accompanying demand for an increase in power density and the necessity to reduce costs in series production, the winding of electric machines and associated production processes are being improved. A promising novel type of winding with numerous advantages is the bar-wound winding, which introduces new demands on technologies for their production. This winding is manufactured from a wide range of preformed elements made of enameled copper wire, that must be connected to each other mechanically and electrically. For this purpose, it is necessary to remove the insulation of the conducting elements in the joining area. Due to the large number of contacts that have to be prepared in this way, it gets essential to use productive and in particular process-safe skinning technologies. In this paper, the motivation for the application of bar-wound windings and the corresponding production chain is expounded. A method for the metrological quality control of insulation residues in the skinned area is qualified and technologies for the realization of the skinning process are compared. In addition, experiments to create process knowledge for the laser-based removal of the insulation and the skinning by means of rotating brushes are presented.
CRIS-Team Scopus Importer:2020-03-20
Keywords: Electric traction drives; Fluorescence based quality assurance; Hairpin winding; Laser-based skinning